Construction of a Test Facility for Demonstration of a Liquid Lead-bismuth-cooled 10 kW Thermal Receiver in a Solar Furnace Arrangement - SOMMER. (May 2015) - Flesch, J.; Fritsch, A.; Cammi, G.; Marocco, L.; Fellmoser, F.; Pacio, J.; Wetzel, Th.
Abstract: Liquid metals have been proposed in the past as high temperature heat transfer media in concentrating solar power (CSP) systems. Until the mid 80s test facilities were operated with liquid sodium-cooled central receivers. After a period of reduced interest in that approach, several new efforts have been reported recently, particularly from the US, South Africa and Australia. In addition, several recent publications have highlighted the attractive properties of liquid metals for CSP applications. A new contribution to this topic has been launched by Karlsruhe Institute of Technology (KIT) and the Solar Institute of the German Aerospace Center (DLR), combining their experience in CSP and liquid metal technology. The overall goals of this project are planning, design, construction and operation of a small concentrating solar power system in the 10 kW thermal range (named SOMMER) using liquid metal as heat transfer fluid for re-gaining operation experience and validating design methodology and providing a complete design concept for a large pilot CSP plant based on liquid metal technology, up to evaluation of O&M cost and levelized cost of electricity. This paper describes the current status of the work on the design and setup of SOMMER, the research goals of this facility, first results of numerical activities in view of the liquid metal cooled receiver design and the connection to the design activities for the pilot plant.